Confirmed case of encephalitis caused by Murray Valley encephalitis virus infection in a horse - Gordon, A.; Marbach, C.; Oakey, J.; Edmunds, G.; Condon, K.; Diviney, Sinead; Williams, David; Bingham, J. (SAGE Publications, 2012)
A five year old Australian stock horse in Monto, Queensland, developed neurological signs and was euthanized after a six day course of illness. Histological examination of the brain and spinal cord revealed moderate to severe, subacute, non-suppurative encephalomyelitis. Sections of spinal cord stained positively in immunohistochemistry with a flavivirus-specific monoclonal antibody. Reverse transcription-polymerase chain reaction assay targeting the envelope gene of flavivirus yielded positive results from brain, spinal cord, cerebrospinal fluid and facial nerve. A flavivirus was isolated from the cerebrum and spinal cord. Nucleotide sequences obtained from amplicons from both tissues and virus isolated in cell culture were compared with those in GenBank, and had 96-98% identity with Murray Valley encephalitis virus. The partial envelope gene sequence of the viral isolate clustered into Genotype 1, and was most closely related to a previous Queensland isolate. This is the first confirmed case of naturally-occurring equine encephalitis attributable to Murray Valley encephalitis virus infection.